Bees of subfamily Nomiinae (Hymenoptera, Halictidae) from Southern Punjab, Pakistan - Huanhuan Chen; Waseem Akram; Muhammad Naeem; Nawaz Haider Bashir; Sabir Hussain; Maryam Riasat; Asif Sajjad; Ruilin Tian; Ammad Ahmad; Muhammad Khalid Rafique; Zamin Hussain Dahri (ZooKeys)
To date, 26 species of the subfamily Nomiinae are known to occur in Pakistan. Among these, most of the species have been reported from the northern parts of Punjab, particularly the Pothwar region. In this study, sweat bees from the subfamily Nomiinae were collected from six districts of southern Punjab, Pakistan, to identify their taxonomic diversity. A total of nine species from four genera i.e., Austronomia Michener, 1965, Lipotriches Gerstaecker, 1858, Nomia Letreille, 1804, and Pseudapis Kirby, 1900 were identified. These species were Austronomia pilipes (Smith, 1875), Lipotriches (Armatriches) fervida (Smith, 1875), L. (Lipotriches) fulvinerva (Cameron, 1907), Nomia (Leuconomia) interstitialis Cameron, 1898, N. (Nomia) curvipes (Fabricius, 1793), N. (Hoplonomia) westwoodi (Gribodo, 1894), Pseudapis (Pseudapis) nilotica (Smith, 1875), P. (Pseudapis) oxybeloides (Smith, 1875), and P. (Nomiapis) bispinosa (Brulle, 1832). All the bee species except P. oxybeloides are reported for the first time from southern Punjab, Pakistan. A key to the genera of the subfamily Nomiinae, species, diagnoses, floral hosts, and distributions are provided. Moreover, habitus photographs and male genitalia illustrations are provided for each species except L. fervida and L. fulvinerva, as no male specimens were collected during the entire study period. This study will be helpful in the establishment of conservation strategies for native bees.